2010
DOI: 10.4161/chan.4.2.10672
|View full text |Cite
|
Sign up to set email alerts
|

Double gaps alongShakerS4 demonstrate omega currents at three different closed states

Abstract: The aim of the present study was to investigate in detail how the voltage sensor in the Shaker potassium channel moves during the gating process. After the publication of the open channel structure from the crystallized K V Ap channel in 2003, an alternative so-called "paddle" model was put forward in contrast to the existing helical screw model. The voltage sensor s4 contains 4 arginine residues relevant for gating, R1(362), R2(365), R3(368) and R4(371), each separated by 2 neutral residues. These charged res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 28 publications
3
30
0
Order By: Relevance
“…To permit an omega current through the Shaker K + channel VSDs requires a “double gap” (absence of arginine in two consecutive positions within S4’s repeating sequence of an arginine at every third position) [Gamal El-Din et al, 2010]. If this were also the case in Hv1, then substitution of N4 with arginine in the R3S background should prevent conduction of Gu + by bracketing the R3 position with arginines: the native R2 immediately before and an introduced R4 immediately after R3.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To permit an omega current through the Shaker K + channel VSDs requires a “double gap” (absence of arginine in two consecutive positions within S4’s repeating sequence of an arginine at every third position) [Gamal El-Din et al, 2010]. If this were also the case in Hv1, then substitution of N4 with arginine in the R3S background should prevent conduction of Gu + by bracketing the R3 position with arginines: the native R2 immediately before and an introduced R4 immediately after R3.…”
Section: Resultsmentioning
confidence: 99%
“…If R3 were positioned in the narrow part of the pore in the activated state, as its homologs are in the VSDs of Shaker [Larsson et al, 1996, Baker et al, 1998, Gamal El-Din et al, 2010] and Kv1.2 [Long et al, 2007] K + channels and Na + channels [Yang et al, 1996, Sokolov et al, 2005], it would be predicted to have a counter-charged partner from one of the other transmembrane segments. The partner residue for R3 in Kv1 channels—a conserved glutamate in the outer third of S2 (E283 in Shaker, E226 in Kv1.2) [Tiwari-Woodruff et al, 2000, Long et al, 2007]—is also present in Na + channels [DeCaen et al, 2008], but is missing in Hv1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results indicate that outward movement of the defective R2 and R3 gating charges into the gating pore upon activation causes an ionic leak through the voltage sensor, which is blocked by repolarization to return them to their resting position. Similarly, Gamal El-Din et al found that paired mutations of two arginine gating charges in Shaker K + channels to smaller residues are generally required to induce gating pore current (Gamal El-Din et al, 2009). The previously observed gating pore current measured for mutations of the R1 gating charge alone (Tombola et al, 2005) depends on the location of a small, uncharged amino acid residue (alanine) in the −3 position (R0) in the Shaker amino acid sequence (Gamal El-Din et al, 2009).…”
Section: Structure-function Studies Of Voltage Sensorsmentioning
confidence: 99%